Local Muslim Heritage: Pelestarian Warisan Budaya Pesantren di Tegalsari Ponorogo - Dawam Multazamy Rohmatulloh (Proceedings of Annual Conference for Muslim Scholars, 2018)
Pesantren Tegalsari Ponorogo is one of the eldest pesantren existed and been a learning place for many popular clerics and public figures in Nusantara, especially in Java. Though this pesantren is currently not even active as a learning institution, its cultural heritage that left by Kiai Ageng Muhammad Besari is still being preserved. By using ethnography-qualitative research method, found that there are still so many of those cultural heritage, in physical form or ritual one. Some of them are kitab kuning manuscripts and ritual of ujud-ujudan, utawen, and shollallohu’ syi’iran. And till nowadays, this preservation act is still dynamically going under variety of support of the society.